Pharmacologic and Hemodynamic Influences on the Rate of Isovolumic Left Ventricular Relaxation in the Normal Conscious Dog - Karliner, Joel S. (1977)
We studied the effects of acute pharmacologic and hemodynamic interventions on isovolumic left ventricular relaxation in 19 conscious dogs using micromanometer tip catheters. Isoproterenol (11 studies) augmented peak rate of rise of left ventricular pressure [(+) dP/dt] by 1,275±227 (SE) mm Hg/s (P < 0.001) and dP/dt at an isopressure point of 35 mm Hg during isovolumic relaxation [(−) dP/dt(35)] by 435±80 mm Hg/s (P < 0.001). Peak (−) dP/dt decreased by 467±89 mm Hg/s (P < 0.002). The time constant, T, derived from the logarithmic fall of pressure during isovolumic relaxation, shortened from 20±2.8 to 14.9±1.8 ms (P < 0.003). Calcium (11 studies) increased peak (+) dP/dt and (−) dP/dt(35) (both P < 0.0001); peak (−) dP/dt was unchanged. T shortened from 20.4±1.8 to 17.3±1.5 ms (P < 0.002). Volume (13 studies) did not affect either dP/dt or T. Phenylephrine (13 studies) augmented peak (−) dP/dt, but reduced (−) dP/dt(35) (both P < 0.01); T lengthened from 22.1±1.5 to 32.5±1.5 ms (P < 0.01). In 15 studies, rapid atrial pacing increased peak (+) dP/dt and (−) dP/dt(35) (both P < 0.01). In the first post-pacing beat, peak (−) dP/dt and (−) dP/dt(35) decreased (both P < 0.01), although peak (+) dP/dt increased further. T paralleled values of (−) dP/dt(35). In five dogs, beta adrenergic blockade had no significant effect on any variable after calcium, volume, or phenylephrine infusion or during or after atrial pacing when the pre-and post-propranolol states were compared. We conclude that positive inotropic interventions augment both left ventricular contraction and relaxation. The changes in isovolumic relaxation are independent of alterations in sympathetic tone produced by beta-adrenergic blockade. Peak (−) dP/dt may not be a valid measure of left ventricular relaxation rate during acute alterations in inotropic state or afterload.